2002
DOI: 10.2169/internalmedicine.41.181
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Procoagulant and Fibrinolytic Markers in Patients with Chronic Obstructive Pulmonary Disease.

Abstract: Objective There is clinical and pathological evidence of thrombosis in pulmonary vessels of patients with chronic obstructive pulmonary disease (COPD). The purpose of this study was to investigate the presence of hypercoagulability and determine the extent of this abnormality in COPDpatients.Patients and Methods Wemeasured plasma levels of thrombin antithrombin III complex (TAT), fibrinopeptide A (FPA), tissue plasminogen activator-plasminogen activator inhibitor (tPA-PAI) : markers of coagulation-fibrinolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 21 publications
5
57
1
2
Order By: Relevance
“…Others have noted increased thrombin-antithrombin III complex, fibrinopeptide A, β-thromboglobulin and tissue plasminogen activator concentrations. 21 Wedzicha and colleagues found increased interleukin 6 and fibrinogen levels in keeping with increased inflammation. 22 During exacerbations, there is evidence of an enhanced inflammation, with an increase in acute phase proteins, complement components, endothelial dysfunction, and variations of haemostasis mechanisms favouring coagulation.…”
Section: Discussionmentioning
confidence: 97%
“…Others have noted increased thrombin-antithrombin III complex, fibrinopeptide A, β-thromboglobulin and tissue plasminogen activator concentrations. 21 Wedzicha and colleagues found increased interleukin 6 and fibrinogen levels in keeping with increased inflammation. 22 During exacerbations, there is evidence of an enhanced inflammation, with an increase in acute phase proteins, complement components, endothelial dysfunction, and variations of haemostasis mechanisms favouring coagulation.…”
Section: Discussionmentioning
confidence: 97%
“…COPD patients show a higher number of platelet-monocyte aggregates, which is indicative of platelet activation; this further increases in AECOPD [21]. Ashitani et al [22] reported an increase in a marker of platelet activation (beta-thromboglobulin) and markers of coagulation-fibrinolysis-system (fibrinopeptide A, thrombin antithrombin III complex, and tissue plasminogen activator-plasminogen activator inhibitor) in 40 COPD patients compared to the control group. They concluded that this clotting factor is an independent predictor of an acute exacerbation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ashitani et al [22] reported an increase in a marker of platelet activation (beta-thromboglobulin) and markers of coagulation-fibrinolysis-system (fibrinopeptide A, thrombin antithrombin III complex, and tissue plasminogen activator-plasminogen activator inhibitor) in 40 COPD patients compared to the control group. They concluded that this clotting factor is an independent predictor of an acute exacerbation [22]. During AECOPD, an exaggerated shift in the hemostatic balance occurs due to an increase in platelet aggregation, which was caused by acute disturbances in gas exchange and hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulable state (Table 2) Some case-control studies have clearly established that, independent of current smoking, plasma levels of fi brinogen and other markers of coagulation are signifi cantly higher in stable COPD patients than in healthy subjects (Alessandri et al 1994;Xie and Wang 1998;Wedzicha et al 2000;Ashitani et al 2002). The increased procoagulant activity in COPD may primarily result from infl ammation.…”
Section: Systemic Infl Ammation (Table 1)mentioning
confidence: 99%